Dementia and metabolic syndrome: a bibliometric analysis - Peng, Tao; Yang, Yifan; Ma, Jingying; Xu, Peili; Xie, Xinchun; Hu, Nan; Yan, Yongmei (Frontiers in Aging Neuroscience, 2024)
Background Dementia is a progressive neurodegenerative condition, while metabolic syndrome (MetS) is characterized by a combination of metabolic abnormalities such as hypertension, high blood sugar, and obesity. There exists a connection and overlap between the two conditions in certain aspects, and both are influenced to varying degrees by the process of aging. This study presents an overview of the current research landscape regarding dementia and MetS through bibliometric analysis. Methods A systematic search was conducted to retrieve relevant literature on dementia and MetS published between 1 January 2000, and 30 November 2023, from the Web of Science Core Collection database. Various bibliometric tools, including VOSviewer, CiteSpace, and the R software package “bibliometrix,” were utilized for analysis. Results A total of 717 articles were identified, showing an upward trend in annual publications. Leading contributors included the United States, Italy, and China, with institutions such as the University of California System at the forefront. The Journal of Alzheimer’s Disease emerged as the top publisher, while research published in Neurology garnered significant citations. Noteworthy authors encompassed Panza, Francesco; Frisardi, Vincenza; and Feldman, Eva L, with Kristine Yaffe being the most cited author (280 citations). Recent studies have focused on themes like “gut microbiota,” “neuroinflammation,” “fatty acids,” and “microglia.” Conclusion This bibliometric analysis summarizes the foundational knowledge structure in the realm of dementia and MetS from 2000 to 2023. By highlighting current research frontiers and trending topics, this analysis serves as a valuable reference for researchers in the field.